Studi Analogi Dan Komparasi Media Pembelajaran Online Bagi Mahasiswa Terhadap Media Dan Proses Pembelajaran Zaman Rasulullah - Putri, Santika Ameylia; Arifin, Imamul; Fadhillah, Wiradika Nur (Edification Journal : Pendidikan Agama Islam, 2022)
During the pandemic, the use of online learning media has increased, especially for students. This is because all access to education has to be done from home to avoid the wider spread of Covid-19. But in fact there are many obstacles and difficulties experienced by students from using online learning media when compared to offline learning media. Online media is quite different from offline media. Before the pandemic, learning was carried out offline by students and lecturers. However, during this pandemic we use electronic devices such as gadgets, laptops, computers, tablets and so on as a means for learning to take place even though it is not in one place. An increasingly sophisticated era presents various technologies and applications that make learning easier during this pandemic. Today's offline learning from the time of the prophet is far different, moreover, online learning and learning at the time of the prophet are certainly very different. At the time of the Prophet Muhammad himself, the use of learning media was already applied, especially in the spread of Islam itself. Therefore, this article that we have compiled aims to provide an overview and comparison of media and the learning process in the present and the era of the Prophet Muhammad, to find out all the advantages and disadvantages of various sides in these two different periods.